A Rare Case of Pancreatic Tuberculosis. Issue 7 (August 2017) - Catalya, Stephen; Tulpule, Sunil; Arshed, Sabrina; Nai, Qiang; Sen, Shuvendu
Abstract : Abstract: Tuberculosis remains a major public health concern, although it has reportedly shown a decline in prevalence both in the United States and abroad in recent years. The focus on diagnosing and treating tuberculosis is on pulmonary tuberculosis. Meanwhile, pancreatic tuberculosis remains exceedingly rare, accounting for less than 5% ( Gastroenterol Rep (Oxf), 2014;2:154–157) of all tuberculosis cases in the developing world. A literature review shows that the head is primarily affected in pancreatic tuberculosis ( Gastroenterol Rep (Oxf), 2014;2:154–157).